Tapuy production from purple rice - Romero, Ronald V.; Azanza, Ma. Patricia V. (2000.)
ABSTRACT This study was conducted to produce tapuy, a local rice wine, using uplanf purple rice as raw material and employing the Benguet method of preparation. The general procedure adapted for tapuy making included cooking of ric by boiling, inoculation of he rice with 1%(w/w) starter culture, and fermentation for 3d. The test parameters considered in the study included selection of best wine produced from 3 starter culture sources from Pangasinan, and determination of the optimum age of the starter culture from the selected source. The best source of starter culture was based on the acceptability rating of the resultant wines. Starter cultures stored within 3-5 weeks produced the most acceptable rice wine. The wine produced by 3-5 weeks old starter culture from the test selected source was described as having a color between violet to red, slightly sweet taste and aftertaste, and was liked slightly overall by 62 panelists. The wine recorded a TPC and YMC of 〖10〗^8 and 〖10〗^7 cfu/ml, respectively. A yield of 85% (L wine/kg rice) relative to raw rice used was recorded. The wine had an alcohol content of 5.46% (v/v) alcohol to wine and with a pH of 3.82. The use of pure culture as starter for wine making was recommended to optimize the process. Moreover, clarification using bentonite and activated charcoal was also recommended.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Rice wines